What the Gospels meant - Wills, Garry, 1934- (New York : Viking, 2008)
Examines the goals, methods, and styles of the evangelists and how these shaped the gospels' messages. The earliest book, Mark, emphasizes Jesus the sufferer; in Matthew, Jesus the teacher; in Luke, Jesus the reconciler; and in John, Jesus the mystic.
Inroduction: What is a Gospel? -- Mark : report from the suffering body of Jesus -- Persecution in Syria -- Messianic signs -- Mark's artistry -- Matthew : report from the teaching body of Jesus -- Birth narrative -- Sermon on the Mount -- Death and resurrection -- Luke : report from the reconciling body of Jesus -- Nativity -- A Jesus for outcasts -- A healing death -- John : report from the mystical body of Jesus -- Word into world -- The inner life -- Life out of death -- Epilogue: How to read the Gospels.
Includes bibliographical references.
Keywords: Bible. -- Criticism, interpretation, etc